Community-led diversion of Indigenous young people from the justice system: the role of government administrative data - Reeve, Rebecca (International journal of law, crime and justice, 2024)
Indigenous communities in Australia have grave concerns about the high rates of incarceration of their young people, and advocate for the need for holistic community-led solutions. This article details the use of administrative data in the evaluation of a model of youth diversion led by an Elders group in a remote community, developed in partnership with a university. The model views effective diversion as addressing all underlying factors driving contact with the justice system for Indigenous young people. The methodology includes linking data from relevant government agencies for holistic understanding of young people's institutional engagement over time, including unmet health, housing, education and disability needs and opportunities for positive pathways. Administrative data has not conventionally been subject to ethical scrutiny nor seen as compatible with community priorities. However, we demonstrate how it can enable communities to investigate questions and build change meaningful to them, and improve evidence and policy.